2010
DOI: 10.1097/npt.0b013e3181fd5eab
|View full text |Cite
|
Sign up to set email alerts
|

Split-Belt Treadmill Training Poststroke

Abstract: Background/Purpose Even after rehabilitation, many individuals with stroke have residual gait deviations and limitations in functional walking. Applying the principles of motor adaptation through a split-belt treadmill walking paradigm can lead to short-term improvements in step length asymmetry after stroke. The focus of this case study was to determine whether it is possible to capitalize on these improvements for long-term gain. Case Description The participant was a 36-year-old female who was 1.6 years p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 40 publications
0
77
0
1
Order By: Relevance
“…These responses, of changing interlimb dynamics over a series of steps during one practice period on the rotating or split-belt treadmill, are a form of motor adaptation; participants are adjusting an already well-learned motor skill over a period of trial-and-error practice, as they are exposed to a novel and perturbing environment (Martin et al 1996b). This adaptation has been extensively studied (Earhart et al 2001;Malone and Bastian 2010;Reisman et al 2005Reisman et al , 2007Reisman et al , 2009Reisman et al , 2010Torres-Oviedo and Bastian 2010;Vasudevan and Bastian 2010) and is thought to be a necessary component of longer-term motor learning (Bastian 2008).…”
mentioning
confidence: 99%
“…These responses, of changing interlimb dynamics over a series of steps during one practice period on the rotating or split-belt treadmill, are a form of motor adaptation; participants are adjusting an already well-learned motor skill over a period of trial-and-error practice, as they are exposed to a novel and perturbing environment (Martin et al 1996b). This adaptation has been extensively studied (Earhart et al 2001;Malone and Bastian 2010;Reisman et al 2005Reisman et al , 2007Reisman et al , 2009Reisman et al , 2010Torres-Oviedo and Bastian 2010;Vasudevan and Bastian 2010) and is thought to be a necessary component of longer-term motor learning (Bastian 2008).…”
mentioning
confidence: 99%
“…According to the results, 50 or more steps were sufficient to maintain a modified muscle activity pattern; thus, the researchers suggested that movement errors would decrease for 24 hours after initial exposure to a novel environment. In addition, short-term modified low extremity movement patterns obtained in perturbation environments can lead to long-term improvement of the CNS (Lam et al, 2011;Reisman et al, 2010). Through these studies, external stimulations such as perturbations were found to change muscle activity patterns and the altered muscle activity patterns were found to remain for a certain amount of time.…”
Section: Discussionmentioning
confidence: 97%
“…In many previous studies, increases in ankle dorsiflexion angles and improvement in gait speed and balance ability could be found when ankle dorsiflexor muscle activity increased during ambulation (Blanchette et al, 2011;Kesar et al, 2010;Lam et al, 2011;Reisman et al, 2010;Richards et al, 1993;Rose et al, 2010;van Swigchem et al, 2011). In addition, the strength and the coordination of ankle muscles such as tibialis anterior and gastrocneminus are important factors to maintain balance (Kaminski and Hartsell;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted by this team and found promising, short term after effects of improved gait symmetry in patients post-stroke. Recently, Reisman produced a case study investing long-term effects using 1-month follow-up data and found asymmetry to continually decrease from baseline to post testing and 1 month follow-up [12].…”
Section: Split-belt Paradigmmentioning
confidence: 98%